Redesain Terminal Bus Cibinong Dengan Fasilitas Shopping Mall Pendekatan Green Architecture - guteris, abdul salim, DR. IR. Dhani Mutiari, MT, Nur Rahmawati Samsiyah ST,MT (2016)
A bus station is certain to have activity economic and deals in a wide range of services, which in turn have economic or financial benefit either directly or inderectly. Is the value or financial results among other is : retribution, rental kios, advertisement services. Bus station is public facilities must also provide services sicial function in this case the travel arrangements, a temporary resting place, restoration, parking, and garden. Social function bus station which inderctly is supporting the development of an area through of land transport infrastucture facilities for the passenger transit activity.